2020
DOI: 10.1016/j.envres.2020.109837
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the current and future distribution of the West Nile virus mosquito vector Culex pipiens in Spain

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 91 publications
(108 reference statements)
5
30
1
Order By: Relevance
“…Considering the former and given that a competent mosquito vector, Cx. pipiens, is widespread in Spain (our results, but also see Bueno-Marí et al, 2012;Gangoso et al, 2020;, the transmission of WNV could be expected in most of the country. However, and regardless of the abundance of a competent vector, the risk of transmission is expected to be very low in areas with unsuitable climatic conditions for the circulation of WNV (such as northwestern Spain, see Figure 6).…”
Section: Discussionsupporting
confidence: 82%
“…Considering the former and given that a competent mosquito vector, Cx. pipiens, is widespread in Spain (our results, but also see Bueno-Marí et al, 2012;Gangoso et al, 2020;, the transmission of WNV could be expected in most of the country. However, and regardless of the abundance of a competent vector, the risk of transmission is expected to be very low in areas with unsuitable climatic conditions for the circulation of WNV (such as northwestern Spain, see Figure 6).…”
Section: Discussionsupporting
confidence: 82%
“…Previous studies have described Cx. pipiens as the most frequent and widespread mosquito species in Extremadura, followed by Culex theileri and Culex univittatus (Gangoso et al., 2020; Mixão et al., 2016), all of them highly competent vectors of WNV.…”
Section: Discussionmentioning
confidence: 99%
“…Authors adapted a suitability index to WNV and found that it confirmed the geotemporal estimation of transmission potential of WNV in the country. Several further studies have been and are investigating the ecological and environmental drivers of WNV [16,17]. Factors associated to national health systems, such as diagnostic awareness and vigilance, diagnostic capabilities and capacities, surveillance and reporting accuracies could also contribute to the annual variations of diagnosed and reported cases in a country.…”
mentioning
confidence: 99%